Gold Nanoparticles in Cancer Treatment and Diagnostics: A Review of Emerging Trends and Therapeutic Potential - Anjali Yadav; Ruchi Bharti (Orbital: The Electronic Journal of Chemistry, 2024)
This comprehensive review delves into the burgeoning role of gold nanoparticles in both cancer treatment and diagnostics. The advent of gold nanoparticle (AuNP) vaccines has opened avenues for therapeutic and prophylactic applications, suggesting the potential to prevent or treat infections and various pathologies. The exceptional efficacy of AuNPs in cancer treatment is a focal point of exploration, with ongoing investigations into their utility for targeted delivery and therapy across diverse cancer types. A distinctive attribute of AuNPs lies in their ability to selectively target cancerous cells while safeguarding healthy cells, attributed to their unique size and shape that facilitate selective accumulation in cancer cells. Upon cellular entry and aggregation, they exhibit prompt activation to eradicate cancer cells. Furthermore, AuNPs possess inherent capabilities to enhance and modulate immune responses, functioning as both an adjuvant and a delivery system. Another advantageous feature is their amenability to functionalization with diverse molecules, including antibodies and drugs, augmenting specificity and effectiveness. This customization enables precise targeting of cancer cells and direct delivery of therapeutic agents to tumor sites, mitigating the adverse effects associated with conventional chemotherapy. Despite ongoing research, the promise of AuNPs as a potent tool in the battle against cancer is evident, underscoring their potential significance in future therapeutic strategies.